Ancestral founder mutations in calpain‐3 in the Indian Agarwal community: Historical, clinical, and molecular perspective. Issue 6 (11th May 2013) - Ankala, Arunkanth; Kohn, Jordan N.; Dastur, Rashna; Gaitonde, Pradnya; Khadilkar, Satish V.; Hegde, Madhuri R.
ABSTRACT Introduction Clinical heterogeneity of limb‐girdle muscular dystrophies (LGMDs, 24 known subtypes), which includes overlapping phenotypes and varying ages of onset and morbidity, adds complexity to clinical and molecular diagnoses. Methods To diagnose LGMD subtype, protein analysis, using immunohistochemistry (IHC) and immunoblotting, was followed by gene sequencing through a panel approach (simultaneous sequencing of known LGMD genes) in 9 patients from unrelated families of the Indian Agarwal community. Haplotype studies were performed by targeted SNP genotyping to establish mutation segregation. Results We identified 2 founder mutations in CAPN3, a missense (c.2338G>C; p.D780H) and a splice‐site (c.2099‐1G>T) mutation, on 2 different haplotype backgrounds. The patients were either heterozygous for both or homozygous for either of these mutations. Conclusions Founder mutations have immediate clinical application, at least in selected population groups. Clinically available gene panels may provide a definitive molecular diagnosis for heterogeneous disorders such as LGMD. Muscle Nerve 47: 931–937, 2013